Vitamin E Binds to Specific Binding Sites and Enhances Prostacyclin Production by Cultured Aortic Endothelial Cells - Kunisaki, Makoto; Umeda, Fumio; Inoguchi, Toyoshi; Nawata, Hajime (Thrombosis and Haemostasis, 1992)
We evaluated the effect of d-α-tocopherol (vitamin E) on the production of prostacyclin (PGI2) by cultured bovine aortic endothelial cells. Vitamin E at physiological doses significantly enhanced the production of PGI2 by aortic endothelial cells when added to the culture simultaneously with histamine, the Ca2+ ionophore A23187 (A23187), plasma-derived serum (PDS), or arachidonic acid. This effect was found to occur in a time- and dose-dependent manner, and the maximal enhancement was produced by 9.28 µM of vitamin E for 1 h incubations. Significantly lower amounts of lipid peroxides were measured in endothelial cells stimulated by 10% PDS with 9.28 µM of vitamin E than in those stimulated without vitamin E for over 24 h, although the stimulation during the initial 1 to 12 h period did not have a significant effect on lipid peroxide formation in cultured aortic endothelial cells.We also demonstrated that bovine aortic endothelial cells have specific binding sites for [3H]vitamin E that exhibited time- and temperature-dependent saturability. At 4° C, the nonspecific binding was 8–12% of the total binding, and the specific binding reached equilibrium by 2 h. Specific binding increased with the concentration of [3H]vitamin E and became saturated at concentrations between 1.5 µM and 2.0 µM per 2.0 × 105 cells. Raising the unlabeled vitamin E concentration from 97.7 nM to 1,000 µM reduced the specific binding of 2.0 µM [3H]vitamin E. The Scatchard plot of [3H]vitamin E binding to the endothelial cells shows two classes of binding sites: one with a high affinity {Ka1 2.48 ± 0.32 × 107 NT-1, n = 6} and a low capacity {n1 1.20 ± 0.34 × 107 sites/cell} and the other with a low affinity Ka2 1.18 ± 0.32 × 105 M–1 and a high capacity {n2 3.39 ± 0.53 × 109 sites/cell}.Our results suggest that the endothelial cells binding sites for vitamin E may play some roles in vascular homeostasis in vivo, and that vitamin E may prevent the development of atherosclerotic changes due in part to the enhancement of PGI2 production by the vascular wall and its action as an antioxidant in vascular endothelial cell.